Prenatal maternal stress shapes children's theory of mind: the QF2011 Queensland Flood Study. (24th March 2017) - Simcock, G.; Kildea, S.; Elgbeili, G.; Laplante, D. P.; Cobham, V.; King, S.
Abstract : Research shows that stress in pregnancy has powerful and enduring effects on many facets of child development, including increases in behavior problems and neurodevelopmental disorders. Theory of mind is an important aspect of child development that is predictive of successful social functioning and is impaired in children with autism. A number of factors related to individual differences in theory of mind have been identified, but whether theory of mind development is shaped by prenatal events has not yet been examined. In this study we utilized a sudden onset flood that occurred in Queensland, Australia in 2011 to examine whether disaster-related prenatal maternal stress predicts child theory of mind and whether sex of the child or timing of the stressor in pregnancy moderates these effects. Higher levels of flood-related maternal subjective stress, but not objective hardship, predicted worse theory of mind at 30 months ( n =130). Further, maternal cognitive appraisal of the flood moderated the effects of stress in pregnancy on girls' theory of mind performance but not boys'. These results illuminate how stress in pregnancy can shape child development and the findings are discussed in relation to biological mechanisms in pregnancy and stress theory.